Pengembangan Instrumen Tes Berpikir Kreatif Pada Materi Gerak Dan Gaya - Moh. Havis; Azizahwati Azizahwati; Muhammad Syafi'i (Universitas Pakuan, 2026)
DEVELOPMENT OF CREATIVE THINKING TEST INSTRUMENTS ON MOTION AND STYLE MATERIALS This study aims to analyze the effectiveness of implementing an interactive module based on Siak local wisdom through the Creative Problem Solving (CPS) learning model in improving students’ creative thinking skills on motion and force material at SMP Negeri 1 Siak. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The research subjects were eighth-grade students selected through purposive sampling. The research instrument was a creative thinking skills test covering fluency, flexibility, originality, and elaboration aspects. Data were analyzed using the normalized gain (N-gain) test to determine the improvement in students’ abilities before and after treatment. The results indicated that the use of an interactive module based on local wisdom combined with the CPS model significantly improved students’ creative thinking skills, with moderate to high improvement categories. Furthermore, learning integrated with local wisdom increased student engagement and contextual understanding of physics concepts. Therefore, this interactive module can serve as an innovative alternative in science learning, particularly physics, to support the development of students’ creative thinking skills.